ANALISIS NILAI PENDIDIKAN MORAL NOVEL REMBULAN TENGGELAM DI WAJAHMU: PENDEKATAN SEMIOTIK PEIRCE - Ahkwan Setiawan; Helena Emma Maria M; Hajrah Hajrah (Universitas Negeri Makassar, 2020)
Analysis of the Moral Education Values of the Moon Novel Sinking in Your Face: Getting Peirce Semiotics This study aims to describe the value of moral education in the novel Rembulan Drowning in Your Face by Tere Liye using Peirce's theory based on icons, indexes and symbols. This type of research is a type of qualitative research. The data of this study are statements or text quotations containing moral education values based on icons, indexes, and symbols. The data source of this research is the 426-page Rembulan Tenggelam di Wajahmu by Tere Liye, first published by Republika. Research data collection using reading, note taking and verbatim techniques. Data analysis by data reduction, data presentation, inference and verification of research results. The results of this study are there are moral education values in the form of iconic markers: rewarding achievement, friendship; topological icon markers: religious, honest, social care, democratic, friendly / communicative, responsibility, peace-loving, caring for the environment, and hard work. The immoral values found are: not loving peace, gambling, stealing, picking pockets.